2001
DOI: 10.1046/j.1472-765x.2001.01012.x
|View full text |Cite
|
Sign up to set email alerts
|

The effect of inoculum size and sublethal injury on the ability of Listeria monocytogenes to initiate growth under suboptimal conditions

Abstract: Aims: To investigate the effect of inoculum size and physiological state on the ability of Listeria monocytogenes cells to initiate growth under suboptimal conditions of salt concentration and pH. Methods and Results: Cell suspensions were serially diluted in media of different salt concentration or pH and replicate inocula distributed into 96-well microplates. The proportion of wells showing growth at each dilution level was determined after incubation for 6 weeks for each set of conditions. Growth occurred f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
40
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(42 citation statements)
references
References 9 publications
2
40
0
Order By: Relevance
“…No growth of the L. monocytogenes strains was observed for the BHI adjusted to pâté conditions after 21 days when a low inoculum level was used. It was established that under more severe stress conditions none of the cultures grew when the inoculum size was too low (less than 10 3 cells) whereas growth is noted with a higher inoculum Pascual et al, 2001). The experiment for the BHI adjusted to pâté conditions was repeated with a high inoculum level (10 7 -10 5 cfu/ml) and these results are shown in Fig.…”
Section: Characterisation Of L Monocytogenes Strains: Response To Sumentioning
confidence: 98%
See 2 more Smart Citations
“…No growth of the L. monocytogenes strains was observed for the BHI adjusted to pâté conditions after 21 days when a low inoculum level was used. It was established that under more severe stress conditions none of the cultures grew when the inoculum size was too low (less than 10 3 cells) whereas growth is noted with a higher inoculum Pascual et al, 2001). The experiment for the BHI adjusted to pâté conditions was repeated with a high inoculum level (10 7 -10 5 cfu/ml) and these results are shown in Fig.…”
Section: Characterisation Of L Monocytogenes Strains: Response To Sumentioning
confidence: 98%
“…A challenge test in which the inoculum contains too many organisms may overstress the preservative system of a product which would not normally be at risk and lead to an overestimation of the risk, whereas too few organisms may give false negative results (Rose and Stringer, 1987). Studies have shown that beneath the common inoculation level of 1000 cfu/ml, the lag phase becomes longer and the probability of growth is less (Gay et al, 1996;Robinson et al, 2001;Pascual et al, 2001). Farber and Daley (1994) found that when L. monocytogenes was present in very low numbers on meats such as sliced ham, turkey breasts, wieners, and pâté stored at 4 jC, its numbers did not increase.…”
Section: Choice Of Inoculum Levelmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, some individual lag time distributions have been characterized (23,33). The variability of individual lag times seems to be wider as microorganisms are injured (4,33,34,39) or as growth conditions are unfavorable (23,24,27).…”
mentioning
confidence: 99%
“…The bacterial lag time is affected by the current environmental conditions, as well as various other factors, such as the history of the population or cell, preculturing conditions, the magnitude and rate of change in the environment (11,21,22,35), initial cell counts (3,27,30), and strain variability. In the present study, we did not employ these factors as parameters; however, we could use the effects of the population history, initial cell counts, and strain variability as parameters in a logistic regression model due to the flexible nature of the model.…”
Section: Discussionmentioning
confidence: 99%